2017
DOI: 10.14257/ijbsbt.2017.9.3.08
|View full text |Cite
|
Sign up to set email alerts
|

Semi Purification and Identifications Molecule Protein Weigh of Alkaline Protease Enzyme from Bacillus cereus LS2B

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Amongst all tested buffers, relative activity of P1 protease fraction was the highest in 200 mM glycine-NaOH buffer (pH 10) as depicted in Figure 10. Dialysis causes diffusion of salt and nonprotein molecules diffuse into the solution (buffer) which has a lower pressure passing through the cellophane dialysis bag [75]. A consistent increase in purification fold and specific activity at each step was observed.…”
Section: Bulk Production and Partial Purification Of P1 Proteasementioning
confidence: 90%
“…Amongst all tested buffers, relative activity of P1 protease fraction was the highest in 200 mM glycine-NaOH buffer (pH 10) as depicted in Figure 10. Dialysis causes diffusion of salt and nonprotein molecules diffuse into the solution (buffer) which has a lower pressure passing through the cellophane dialysis bag [75]. A consistent increase in purification fold and specific activity at each step was observed.…”
Section: Bulk Production and Partial Purification Of P1 Proteasementioning
confidence: 90%
“…A study conducted in probiotics showed the three predominant protein molecules from the SDS-Page of Hi Trap ion exchange 21 . The loss of non-protein compound of protease enzymes seen with weight of 34 kDa, 17 kDa, 13 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus cereus TD5B [11][12][13], Bacillus cereus LS2B [14][15][16] and Pseudomonas sp. PK-4 [17] was maintenance at the Laboratory of Leather Technology, By-products, and Livestock Waste, Gadjah Mada University.…”
Section: Indigenous Strains and Medium Preparationmentioning
confidence: 99%
“…PK-4 [17] was maintenance at the Laboratory of Leather Technology, By-products, and Livestock Waste, Gadjah Mada University. The strains originate from the soil at the chicken farm and Local Slaughterhouse [14,15]. One ose of the strains was input into the Pre-culture medium and incubated on a Rotary shaker at 120 rpm for 18 hours.…”
Section: Indigenous Strains and Medium Preparationmentioning
confidence: 99%